Lausanne Conference : Peacemaking process and Parliamentary Politics in Ankara, 1922-1923 - PAPUÇÇULAR, HAZAL (My University, 2019)
Lausanne Treaty of Turkey is a product of Turkish national movement, which was organized after the end of the World War I and led by a newly founded parliament in Ankara. In Turkish historiography, this parliament has usually been associated with its revolutionary character that paved the way for a new Turkish state and with its democratic setting in which different viewpoints existed and clashed with each other even in the matters of vital importance. In this sense, this paper aims to analyze the relationship between parliamentary politics and peace making efforts of Turkish delegation in Lausanne. It shows the parliamentary opposition to the peace-making process of Turkey which existed in many issues pertaining to the composition and attitude of the Turkish delegation in Lausanne, drawing o f the borders, future of the Straits, and economic/fmancial matters. Apart from being a specific analysis of intra-parliamentary politics on peace and war, this paper exemplifies a broader understanding: the relationship between domestic policy and peace-making process. In the Turkish case, although the intra- parliamentary opposition would not change the outcome, it would complicate the peace-making efforts of the Turkish delegation in Lausanne and question the leadership in Ankara. In return, it would be one of the reasons for parliamentary elections in Turkey held in 1923. While dealing with the national politics on the negotiation process in Lausamie, this paper also will mention how these discussions on Lausanne made nearly a century ago influence the discourses in Turkey even today where Lausanne Treaty is still being discussed vividly in domestic politics.